Differences in free sterols content and composition associated with somatic embryogenesis, shoot organogenesis and calli growth of flax - Cunha, Ana (1997)
A single medium was used for induction of somatic embryogenesis and shoot organogenesis from flax hypocotyls. With this system, a comparative study was performed to determine the free sterols content and composition in non-organogenic, shoot organogenic and embryogenic calli as well as in regenerated shoots and somatic embryos grown under the same hormonal supplementation. The induction of somatic embryogenesis and shoot organogenesis of flax was associated with an increase of total sterols in the competent calli and an increased ratio of stigmasterol to β-sitosterol in derived embryos and shoots. On the contrary, in non-organogenic calli, the ratio stigmasterol to β-sitosterol decreased during the exponential growth phase due to a drastic rise in the β-sitosterol content. This effect as well as the calli growth were higher with 0.5 mg/l 2,4-D than with 0.6 mg/l IBA.